88 What are the psychological needs of caregivers of people with dementia at the end of life?. (14th March 2023) - Lewis, Juliette; Harris, Dylan
Abstract : Background: The WHO recognises dementia as a global health priority. The incidence and prevalence of dementia is increasing exponentially and neither health nor social care services are able to meet the needs of people with dementia (PWD) at the end of life (EOL) without the help of informal caregivers. To date, research has demonstrated the high rates of caregiver burden, anxiety and depression but offers little evidence of how best to ameliorate these issues. The aim of this study was to identify the psychological needs of caregivers of PWD at EOL. Method: A systematic review adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines and narrative synthesis were conducted. Population: adult (aged >18 years) informal caregivers of a formally-diagnosed PWD. Inclusion: English-language studies of psychological needs of caregivers of PWD at EOL. The electronic databases searched were APA PsycINFO, Ovid AMED, CINAHL by EBSCO, Cochrane Database, Ovid EMBASE, Ovid EMCARE and Ovid MEDLINE. Results: Eleven studies met the inclusion criteria; ten qualitative studies and one mixed-methods study. These studies captured the experiences of 356 caregivers. Data extraction identified 80 findings and data synthesis resulted in 22 categories of psychological needs. A narrative synthesis found six key themes: i) relationship-orientated psychological needs; ii) support needs; iii) information needs to support psychological wellbeing; iv) care of the caregiver and the need to maintain caregiver wellbeing; v) the need for role recognition and an identity outside of the caregiving role and vi) psychological security. Conclusion(s): Elucidating the psychological needs of caregivers of PWD at EOL is the first-step in being able to improve the quality of life of caregivers of PWD by identifying targets for the help and support they need when providing care for PWD at EOL. Future research should focus on interventions that might address these needs.